Let the price of item a=x.
So, price of item b=x+1
From the given condition 5a+6b=32.60
Plugging value of a and b.
5x+6(x+1)=32.60
5x+6x+6=32.60
11x+6=32.60
11x=32.60-6
11x=26.60
x=26.60/11=2.42
Cost of item a=$2.42 and cost of item b=$2.42+$1=$3.42
item b cost $1 more than item a.peter purchased 5 of item a and 6 of item b. the total expenditure is $32.60.what is the cost of item a and item b?
Let cost of item a = $x
So, cost of item b = $(x+1)
Now,
5x+6(x+1)=32.60
5x+6x+6=32.60
11x=26.60
i.e. x=$2.42
Therefore cost of item a = $ 2.42
cost of item b = 2.42+1= $3.42